High-latitude diversification within Eurasian least shrews and Alaska tiny shrews (Soricidae) - Hope, Andrew G.; Waltari, Eric; Dokuchaev, Nikolai E.; Abramov, Sergey; Dupal, Tamara; Tsvetkova, Albina; Henttonen, Heikki; MacDonald, S. O.; Cook, Joseph A. (Journal of Geophysical Research: Atmospheres, 2010)
A novel shrew was discovered recently in Alaska and described based on morphological characters as Sorex yukonicus . This species is closely allied to Sorex minutissimus , a widespread shrew ranging through Eurasia. Together their distribution spans Beringia, a large Pleistocene nonglaciated area that connected Asia and North America. Beringia was repeatedly divided due to raised sea levels during Pleistocene interglacials and subsequently reconnected during glacials. We tested predictions related to the influence of large-scale geologic events on genetic variability through a phylogeographic analysis of both species of shrew using evidence from 3 independent genetic loci. We found low genetic divergence between S. minutissimus and S. yukonicus across continents. However, major phylogeographic breaks were found for Eurasian and Maritime Northeast Asia populations. Neither species is reciprocally monophyletic for any of the loci examined. Coalescence times for all pairwise population comparisons within both species fall within the Wisconsinan–Weichselian glacial (<130 thousand years ago), and significant population expansion estimates date to the Holocene suggesting that divergence between these taxa is minimal and may not warrant recognition of 2 distinct species. Phylogeographic relationships and sequence divergence estimates place populations of North American S. yukonicus and Siberian S. minutissimus as most closely related, and together they are sister to European S. minutissimus . We conclude that populations east and west of the Bering Strait represent a single Holarctic species, S. minutissimus . Temporal changes in range based on ecological niche predictions and a comparative assessment of other codistributed taxa provide a preliminary view of potential Last Glacial Maximum refugia in northern Asia.